Interventions that prevent or reduce obesity in children from birth to five years of age: A systematic review. (June 2021) - Narzisi, Katia; Simons, Joan
Childhood obesity worldwide affects 5.6% or 38.3 million children under five years of age. The longer children are overweight or obese, the more likely they are to become obese adults with all the contingent morbidity involved. An extensive number of preventive interventions to combat childhood obesity have been carried out worldwide. This article reports a systematic review of interventions aimed to reducing or preventing obesity under-fives. The search was performed with six different databases: Web of Science, PsycINFO, Cochrane, PubMed, Medline, and CINAHL. Studies meeting the inclusion criteria were independently assessed using Joanna Briggs Institute methodology. Thirty studies involving 23, 185 children across nine countries were included. Twenty-two were randomised controlled trials, and 8 quasi-experimental pretest/post-test design with comparison. These studies fell into four different categories: home-based interventions with family involvement ( n = 12), preschool/early childhood settings ( n = 9), multicomponent interventions across multiple settings ( n = 6) and healthcare setting ( n = 3). Future research should focus on increasing the accessibility of education on diet and physical activity for deprived families as well as the cultural acceptability of interventions to prevent childhood obesity.